Characterization of non-uniform field aging in asphalt pavements. (30th October 2017) - Yin, Fan; Epps Martin, Amy; Arámbula-Mercado, Edith; Newcomb, David
Highlights: The non-uniform field aging of asphalt mixtures was observed in the pavement structure. The surface of the asphalt pavement aged faster than the bottom. Mixture stiffness and binder property gradients with pavement depth were characterized. The non-uniformity of field aging increased with pavement in-service time and temperature. Abstract: Although extensive work has been performed to quantify field aging of asphalt pavements and to evaluate its effect on asphalt mixture properties, little effort has been devoted towards characterizing the non-uniform field aging of asphalt pavements through laboratory testing. Due to the non-uniform air void and temperature distribution in the pavement structure, the surface of the pavement ages faster than the bottom; thus a field aging gradient exists. In this study, field cores obtained from four field projects at various in-service times were tested in the non-destructive Viscoelastic Characterization Direct Tension test to determine their mixture stiffness gradient with pavement depth. In addition, asphalt binders were extracted and recovered from the field cores at different pavement depths and then tested with the Dynamic Shear Rheometer and Fourier Transform Infrared Spectroscopy to differentiate their rheological and chemical properties. Test results obtained in this study provided a better understanding of the non-uniform field aging in asphalt pavements and its effect on asphalt binder and mixture properties.